How do lead auditor instructions influence component auditors' evidence collection decisions? The joint influence of construal interpretations and responsibility - Zhu, Skye; Phang, Soon‐Yeow (Contemporary Accounting Research, 2024)
Abstract Regulators have raised concerns about the quality of component auditors' work. Of particular concern is that component auditors often do not adequately perform procedures and gather enough quality evidence. This failure is likely caused by component auditors' different interpretations of lead auditor instructions and by their lack of responsibility. Our interview findings suggest that component auditors tend to interpret lead auditor instructions concretely because they often receive detailed instructions from lead auditors. We propose that a responsibility prompt reminding component auditors to be aware of their obligations to the group audit engagement can improve their evidence collection. In two experiments, we find that our proposed responsibility prompt can effectively improve component auditors' evidence collection decisions and that this finding holds across different cultural settings. Our third experiment provides evidence that a responsibility prompt improves component auditors' evidence collection when provided to auditors who receive instructions that prime low‐level (but not high‐level) construals. Overall, our findings suggest that prompting component auditors to internalize the responsibility of a group audit engagement is a viable way to improve the quality of group audits.